Ancaman Keberfungsian Sosial Pada Masyarakat di Dalam Kawasan Konservasi: Studi Kasus Desa Ranupani di Taman Nasional Bromo Tengger Semeru - Versanudin Hekmatyar; Anggiana Ginanjar Adinugraha (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2021)
Abstract: The objective of this study is to describing the social functioning of the community in the Bromo Tengger Semeru National Park area. Qualitative approach was used to collect the data to be descriptively presented. Social functioning is an important field of life quality measures related to the fulfillment of basic needs. The results show that the threat of social functioning in the Ranupani Village community was influenced by (1) the ability of the community to meet basic needs, (2) the ability to carry out social roles, (3) the adaptability of the community in facing changes, and (4) the integration capabilities in social systems. In the end, community as the main actor will try to maintain and improve its position and role by constructing and acting to reproduce the position in that social environment. Keywords: Social functioning, Access, National Parks, Bromo Tengger Semeru, Ranupani Village